2023
DOI: 10.15835/nbha51213124
|View full text |Cite
|
Sign up to set email alerts
|

In vitro direct organogenesis of the medicinal single-mountain local prioritized vulnerable Greek endemic Achillea occulta under different medium variants

Abstract: Achillea species are of high medicinal value based on their use in traditional medicine and their content in secondary metabolites with potential application in dermatology and cosmetic industry. Achillea occulta is a single-mountain local prioritized vulnerable Greek endemic encountering propagation problems through seeds and root division. In vitro propagation can be used for the rapid and mass production of clonal plants complying with phytochemical and sanitary quality criteria. In this study, several cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Numerous studies have demonstrated that IBA is more effective in promoting adventitious root growth than Indole -3acetic acid (IAA). This effect has been attributed to its higher tissue and solution stability, increased resistance to photodegradation, biological inactivation, and adhesion to the shoots (Sarropoulou et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have demonstrated that IBA is more effective in promoting adventitious root growth than Indole -3acetic acid (IAA). This effect has been attributed to its higher tissue and solution stability, increased resistance to photodegradation, biological inactivation, and adhesion to the shoots (Sarropoulou et al, 2023).…”
Section: Introductionmentioning
confidence: 99%